Poorness and richness. The right to be aided and the right to resist in Hegel - Vieweg, Klaus (Estudios de Filosofía, 2009)
In the Philosophy of Law, Hegel devotes special attention to one of the most worrying problems of modern societies and states: the unbalanced distribution of richness and its consequent chain of social inequalities and unjustness. In his analysis, Hegel stresses the idea that the conformation of a just civil society and a rational state or state of law, depends entirely on the Recognizance, on the part of these spheres, of the Rights of all the individuals who shall enjoy with dignity material possessions, that will enable them not only the assurance of the material conditions of existence, but also the participation and enjoyment of material and spiritual goods that sustain and give dynamics to “life in common”. According to Hegel's diagnosis, such a Recognizance has, certainly, its point of departure in the realms of Abstract Law and stretches into the realm of Morality, in which realms the individual is recognized as a person and as a moral being, but it is only in the superior realm of Ethics where the Recognizance of all the rights that guarantee an honorable life, acquires universal validity and need, since it is this said sphere, concretely in the sphere of the state, where the said Recognizance can take a hold in the different legal and juridical stances that conform it. Such is the path through which the Political Philosophy of Hegel tries to offer a solution to a problem that, such as the one pointed out, is still a threat to societies at present and questions the selfsame structures of power. Independently of the viability of the offered solution, the Political Philosophy of Hegel begs for a pertinent and unquestionable actuality.